CONSISTENCY BETWEEN TEACHERS’ PERCEPTION AND IMPLEMENTATION: AN ANALYSIS OF PEDAGOGICAL CONTENT KNOWLEDGE IN ENGLISH PRIMARY CLASSROOM - Utari, Dewa Ayu Yuri Dianita; Utami, I.G.A.L.P; Utami, I.A.M.I (Universitas Pendidikan Ganesha, 2021)
AbstractThis study aimed at analyzing primary teachers’ perception toward pedagogical content knowledge (PCK) and the implementation in teaching English to young learners in Jembrana regency. This study also aimed at analyzing the consistency between teachers’ perception and the implementation and exploring problems that might be encountered by the teachers. There were 3 primary teachers in Jembrana who involved in this study. This study was embedded mixed method design dominant qualitative which used questionnaire, observation sheet, and interview guide in collecting the data. The result showed that there was no consistency between teachers’ perception and their implementation of PCK. Teachers’ perception was very strong but the implementation was very low. The interview result showed that there were several problems faced by the teachers, such as the non-English background teachers do not mastering English, lack of experience in teaching English, difficult to find an appropriate media, and lack of time in teaching. Keywords: Teachers’ perception, implementation, Pedagogical Content Knowledge